2004
DOI: 10.1038/nature02742
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin relocation from sites of chromosomal loading to places of convergent transcription

Abstract: Sister chromatids, the products of eukaryotic DNA replication, are held together after their synthesis by the chromosomal cohesin complex. This allows the spindle in mitosis to recognise pairs of replication products for segregation into opposite direction1-6. Cohesin forms large protein rings that may bind DNA strands by encircling7, but the characterisation of cohesin binding to chromosomes in vivo has remained vague. Here, we present high resolution analysis of cohesin association along budding yeast chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
637
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(702 citation statements)
references
References 31 publications
47
637
9
Order By: Relevance
“…We favor the first possibility. No report to date has shown that cohesin is enriched at centromeres prior to mitosis in metazoa, although this is the case in yeast (e.g., Lengronne et al 2004). Thus, centromeric cohesin enrichment may be the result of preferential dissociation of cohesin from chromosome arms and protection at centromeres.…”
Section: Discussionmentioning
confidence: 94%
“…We favor the first possibility. No report to date has shown that cohesin is enriched at centromeres prior to mitosis in metazoa, although this is the case in yeast (e.g., Lengronne et al 2004). Thus, centromeric cohesin enrichment may be the result of preferential dissociation of cohesin from chromosome arms and protection at centromeres.…”
Section: Discussionmentioning
confidence: 94%
“…In S. cerevisiae, cohesin does not colocalize with the Scc2 ortholog of Nipped-B on chromosomes (Lengronne et al 2004). Nevertheless, purification of yeast Scc2-Scc4 complex brings along small amounts of cohesin subunits, and thus it has also been proposed that the Scc2-Scc4 complex also directly regulates binding of cohesin to chromosomes (Arumugam et al 2003).…”
Section: Does Nipped-b Directly Regulate Cohesin Function?mentioning
confidence: 99%
“…Nevertheless, purification of yeast Scc2-Scc4 complex brings along small amounts of cohesin subunits, and thus it has also been proposed that the Scc2-Scc4 complex also directly regulates binding of cohesin to chromosomes (Arumugam et al 2003). It is suggested that cohesin loads at Scc2-binding sites and translocates away (Lengronne et al 2004). In contrast, chromatin immunoprecipitation experiments using cultured Drosophila cells reveals that Nipped-B colocalizes with cohesin in the entire nonrepetitive genome, confirming that their colocalization is not unique to polytene and meiotic chromosomes (Misulovin et al, submitted for publication).…”
Section: Does Nipped-b Directly Regulate Cohesin Function?mentioning
confidence: 99%
“…Cohesin is largely excluded from repressed regions of the Drosophila genome that are marked by Polycomb protein binding and trimethylation of lysine 27 of histone H3 (H3K27me3) [46]. In stark contrast to Drosophila, yeast cohesin is excluded from actively transcribed genes and instead accumulates between convergently transcribed genes [47,48] [51].…”
Section: Cohesin and Transcription -Friend Or Foe?mentioning
confidence: 99%
“…Cohesin is largely excluded from repressed regions of the Drosophila genome that are marked by Polycomb protein binding and trimethylation of lysine 27 of histone H3 (H3K27me3) [46]. In stark contrast to Drosophila, yeast cohesin is excluded from actively transcribed genes and instead accumulates between convergently transcribed genes [47,48]. In the fission yeast S. Pombe, cohesin even functions as a terminator of RNA polymerase progression, and is recruited to sites of convergent transcription by the RNA interference (RNAi) transcriptional gene-silencing pathway [49].…”
mentioning
confidence: 99%